Effect of Composition of Transition Metals on Stability of Charged Li-rich Layer-structured Cathodes, Li1.2Ni0.2-xMn0.6-xCo2xO2 (x=0, 0.033, and 0.067), at High Temperatures. (20th December 2015) - Konishi, Hiroaki; Hirano, Tatsumi; Takamatsu, Daiko; Gunji, Akira; Feng, Xiaoliang; Furutsuki, Sho
Highlights: Stability of charged Li1.2 Ni0.2- x Mn0.6- x Co2 x O2 at high temperature was higher than that of charged LiNi0.8 Co0.2 O2 . Stability of charged Li1.2 Ni0.2- x Mn0.6- x Co2 x O2 was improved by substituting Co with Ni and Mn. Oxygen release behavior from charged Li1.2 Ni0.2- x Mn0.6- x Co2 x O2 at high temperature changed during cycles. Abstract: Li1.2 Ni0.2- x Mn0.6- x Co2 x O2 ( x =0, 0.033, and 0.067) cathodes were synthesized and their electrochemical properties and stabilities at high temperature were investigated. As cobalt content x decreased, discharge capacity slightly decreased. However, even non-cobalt-content cathode exhibited high capacity (> 240 Ah kg −1 ). Oxygen release from charged Li1.2 Ni0.2- x Mn0.6- x Co2 x O2 ( x =0, 0.033, and 0.067) at high temperatures was evaluated with thermal desorption spectroscopy-mass spectroscopy (TDS-MS) and it was compared with that from a charged conventional Ni-based layer-structured cathode, LiNi0.8 Co0.2 O2 . The oxygen release from charged Li1.2 Ni0.2- x Mn0.6- x Co2 x O2 ( x =0, 0.033, and 0.067), especially that from a non-cobalt-content cathode, was much less than that from charged LiNi0.8 Co0.2 O2 . This indicated that the stability of charged Li1.2 Ni0.2- x Mn0.6- x Co2 x O2 ( x =0, 0.033, and 0.067) was high, and it was further improved by substituting cobalt with nickel and manganese. The results obtained from X-ray absorption fine structure (XAFS) measurements suggested that the stability of the high-oxidation state of manganese was higher than those of nickel and cobalt. Furthermore, cobalt ions easily migrated from octahedral to tetrahedral sites, and formed spinel-like structure upon heating. In contrast, manganese ions occupied octahedral sites at high temperature. Therefore, as the manganese content increased and the total amount of nickel and cobalt decreased, the structure in a fully charged state was stabilized.